Some Properties for Solutions of Riemann-Liouville Fractional Differential Systems with a Delay. (21st October 2018) - Zhao, Jing; Meng, Fanwei
Abstract : In this paper, we study properties for solutions of Riemann-Liouville (R-L) fractional differential systems with a delay. Some results on integral inequalities are first presented by Ho ¨ lder inequality. Then we investigate properties on solutions for R-L fractional systems with a delay by using the obtained inequalities and obtain upper bound of solutions. Finally, an illustrative example is considered to support our new results.